ANALISIS PENGARUH SERTA UPAYA PENINGKATAN KINERJA KARYAWAN TERKAIT DENGAN KOMUNIKASI, LINGKUNGAN DAN KEPUASAN KERJA (Studi Kasus Pada PT. PG. Rajawali 1 Unit PG. Krebet Baru Bululawang Malang) - Noor, Mariam (DINAMIKA DOTCOM, 2013)
This research intent to know communication influences, environmentally, and job satisfaction for employee performance. Analysis tech data that utilized by structural modeling equation. Base analysis result points out that communication and influential job satisfaction significant for performance to fire an employee. Meanwhile work condition not significant ascendant for employee performance.Â Â Keywords : communication, environmentally, job satisfaction, employee performanceÂ